Manejo agronomico de phaseolus vulgaris l. en condiciones de invernadero en chocope – La Libertad - Reyes Juárez, Paolo Edmundo (2016)
This study was conducted in the district of Chocope, Ascope province, department of La Libertad, for the purpose of describing the agronomic management of string beans (Phaseolus vulgaris L.) under greenhouse conditions. The experiment was conducted from January to March 2016, as genetic material milling I. variety was used and was to describe the different agronomic activities during the crop development. Also, performance parameters was evaluated as plant height, average number of pods per plant, average weight and length of pods per plant and crop yield expressed in kg ha-1. Cultivating vainita under greenhouse conditions development will adequately reaching the end of the crop an average plant 41.17 cm high, and the requirements for harvest at 56 days after sowing, the average length of the fruit harvested was 14.57 cm; the number of pods per plant was harvested 7; the average weight of fruits per plant was 4.2 grams, which allows to estimate a yield per hectare of 1110 kg.